Android-Based Multimedia Development and Worthiness for Economic Learning in High School - Ratna Tiharita Setiawardhani (AL-ISHLAH: Jurnal Pendidikan, 2021)
The Covid-19 pandemic has turned face-to-face learning into online learning, thereby minimizing interactions with other people. So that online learning requires preparation, including appropriate learning media. This study used the ADDIE development method to develop android-based multimedia in the tenth grade of high school economic subjects.  The steps are taken consist of  Analysis, Design, Development, Implementation, Evaluation. The stage consists of learning technical analysis and curriculum analysis. The design stage is the design of android-based media. Media and material expert validation carry out the development stage, the media implementation stage is tested in a limited class, and the evaluation stage is the finalization stage of the media used. The results showed that developing android-based multimedia in tenth high school economics learning met validity, effectiveness, and practice criteria.